Developing complexity science-problem based learning model to enhance conceptual mastery - Finga Fitri Amanda; Sutiman Bambang Sumitro; Sri Rahayu Lestari; Ibrohim Ibrohim (Intelektual Pustaka Media Utama, 2022)
Implementing a proper learning model during the post COVID-19 pandemic is fundamental for learning quality enhancement, specifically for students' conceptual mastery. The research aims to develop a Complexity Science- Problem Based Learning (CS-PBL) model assisted by the Sistem Informasi Pengelola Pembelajaran (SIPEJAR) e-learning platform that is valid, practical, and effective to enhance students' conceptual mastery during the post COVID-19 pandemic. The research and development model were adapted from Plomp and Nieven consisted of three phases: preliminary research, prototyping phase, and assessment phase. The first phase research result was that the learning process in during COVID-19 pandemic was less interactive, which led to less effective learning. The students' score on conceptual mastery was in the poor category. The second phase resulted in a book of CS-PBL model assisted by SIPEJAR and supporting instruments considered valid by three experts. The third phase result was that the CS- PBL model assisted by SIPEJAR was considered practical in the learning process implementation. The CS-PBL model can enhance students' conceptual mastery where the N-gain was sufficiently effective. It is concluded that the CS-PBL model assisted by SIPEJAR was considered valid, practical, and effective to enhance students' conceptual mastery during the post COVID-19 pandemic.